Design and Implementation of A Web-Based Information System for University Staff Union - Muhammad, Muhammad Bala; Lawan, Abdulmalik Ahmad; Abdulrahman, Salisu Mamman (UUM Press, 2024)
The Academic Staff Union of Universities (ASUU) in Nigerian public universities has long championed the welfare and interests of academic staff. However, operational ineffciencies stemming from manual processes hinder its effectiveness in addressing contemporary challenges. This ineffciency hampers ASUU’s effectiveness and limits its ability to interact effciently with its members and stakeholders. Therefore, this study proposes that the ASUU Web-Based Information System (AWBIS) should modernize data management, communication, and decision-making within the union. Drawing on related work in online information systems across various sectors, the methodology involves requirements gathering, leading to the development and implementation of AWBIS Leveraging development technologies, AWBIS offers modules for member management, communication, event organization, and biometric attendance. This project uses the waterfall model approach to developing software as the research methodology. The data collection techniques include interviews and questionnaires. The AWBIS enables various operations to be performed online, consisting of registering members by the admin, logging members, and allowing members to manage their profles. The system also provides a login page for both members and admins, each with their own username and password. A secure and accessible database for storing member profles, academic information, and other relevant data was created. The successful implementation of AWBIS will signifcantly streamline ASUU’s operations, resulting in improved communication, reduced administrative burden, and enhanced transparency. Members will have access to up-to-date information, and the system will facilitate better coordination of ASUU’s activities. Future enhancements, including fnancial management, election processes, loan applications, and mobile app development, are suggested to further optimize AWBIS’s functionality and accessibility. AWBIS is a model for leveraging technology to advance organizational effciency and effectiveness within the education sector